Wilson’s disease in a child: a difficult path to diagnosis (clinical case) - O.M. Вabadzhanian; O.V. Shutova; N.V. Pavlenko; I.G. Solodovnychenko; K.V. Voloshyn (Zdorovʹe Rebenka, 2025)
The article presents data on the etiology, pathogenesis and clinical manifestations of Wilson’s disease, and also describes a diagnostically complex clinical case and own observation of a patient with Wilson’s disease. Wilson’s disease is a chronic liver disease caused by impaired copper metabolism, which can progress to fulminant hepatic failure, chronic hepatitis or liver cirrhosis. In childhood, the disease has a latent course for a long time, it is clinically characterized by signs of liver damage at the initial stage mainly. Based on the review of scientific medical literature and the results of our own observation of a child with Wilson’s disease, it was demonstrated that there are still difficulties in early diagnosis. The problem is due to pronounced clinical polymorphism and insufficient vigilance of practicing physicians regarding this disease. Currently, the generally accepted standard for diagnosing Wilson’s disease is molecular genetic testing and a decrease in ceruloplasmin serum level. However, despite the high specificity of the common standard indicators, none of the above tests can have an independent diagnostic value. Establishing a reliable diagnosis is ensured only by a combination of various clinical, biochemical and genetic tests. Timely diagnosis and treatment of pediatric patients with Wilson’s disease remains important. The use of laboratory tests (levels of copper in daily urine, ceruloplasmin in blood serum), consultations of an ophthalmologist, neurologist and genetic research to detect mutations of the ATP7B gene allows making a timely diagnosis of Wilson’s disease, prescribing an adequate course of treatment. For earlier detection of Wilson’s disease, secondary prevention of liver cirrhosis, and improvement of patients’ quality of life, it is necessary to study the indicators of copper metabolism in all children with unspecified etiology of chronic hepatitis.